Online monitoring of voltage stability margin and its control through STATCOM - Sahu P.; Verma M.K. (My University, 2025)
Voltage instability has been of serious concern for researchers and utilities since last few decades as several incidences of system blackout initiated by voltage instability have been observed in different parts of the world. With advent of synchrophasor technology, it seems possible to monitor and control voltage stability of the system in real time framework. This paper proposes online monitoring of voltage stability margin based on optimally placed phasor measurement units (PMUs), and its control through Static Synchronous Compensator (STATCOM). STATCOM has been placed at the critical bus obtained based on minimum real and reactive power loadability for majority of line outages. STATCOM injects reactive power to the bus based on deviation of bus voltage from its reference value. Bus voltages are determined at regular intervals using measurements obtained by PMUs, and reactive power is injected to the bus online, accordingly. Enhanced voltage stability margin as a result of reactive power injection by STATCOM is monitored at regular interval. Effectiveness of proposed approach of online monitoring and control of voltage stability margin has been validated based on simulations carried out on IEEE 14-bus system, New England 39- bus system and a practical Indian system representing power network of nine states and union territories of Indian system. © 2019 COMPUSOFT, An international journal of advanced computer technology.